^{-n} = a^{0-n} = a^{0} / a^{n }= 1 / a^{n}. Here, in the second equality, the first of your stated rules was used, and in the last equality, the rule a^{0} = 1 for a ≠ 0 was used.

Jane K.

asked • 09/18/19# Explain how the rule that states that a^-n = 1/a^n is consistent with the rules that a^m/a^n = a^m-n and a^0 = 1 for a≠0.

Explain how the rule that states that a^{-n} = 1 / a^{n} is consistent with the rules that a^{m}/a^{n}= a^{m-n} and a^{0} = 1 for a≠0.

Follow
•
1

Add comment

More

Report

## 1 Expert Answer

## Still looking for help? Get the right answer, fast.

Ask a question for free

Get a free answer to a quick problem.

Most questions answered within 4 hours.

#### OR

Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.